2017
DOI: 10.1177/1351010x17744734
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of indigenous and foreign speech in a noisy classroom: A case of primary school pupils

Abstract: This study examines the level of speech recognition of English and Igbo utterances by 70 grade four children. The children, whose mother tongue is Igbo and aged between 8 and 10 years, had English monosyllabic words as well as Igbo monosyllabic and disyllabic words dictated to them in noisy and quiet classrooms. The results show that in noise, their level of recognition was significantly higher for English utterances (p < 0.05) while in quiet, it was significantly higher for Igbo (p < 0.05). Thus, the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…4,39 Previous studies have also shown that noise at high levels had effect on word reminding, more fatigue, and less motivation compared with low levels. 40,41 The results showed that the response time to the stimuli decreased when noise pressure levels were increased, which may be due to the fact that the participants wanted to get rid of this discomfort situation sooner. The results also showed that in the presence of loud noise compared with silence, the response rate to the stimuli increased, but the accuracy decreased.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4,39 Previous studies have also shown that noise at high levels had effect on word reminding, more fatigue, and less motivation compared with low levels. 40,41 The results showed that the response time to the stimuli decreased when noise pressure levels were increased, which may be due to the fact that the participants wanted to get rid of this discomfort situation sooner. The results also showed that in the presence of loud noise compared with silence, the response rate to the stimuli increased, but the accuracy decreased.…”
Section: Discussionmentioning
confidence: 96%
“…4,39 Previous studies have also shown that noise at high levels had effect on word reminding, more fatigue, and less motivation compared with low levels. 40,41…”
Section: Discussionmentioning
confidence: 99%